A new Cylindromorphoides Kerremans, 1903 from the “Gran Sabana” in Venezuela (Coleoptera: Buprestidae) - Hornburg, Michael (Zootaxa, 2003)
From the "Gran Sabana", in southern Venezuela, a new species of the Neotropical buprestid genus Cylindromorphoides Kerremans, 1903, is described. Cylindromorphoides katrinae sp. n. is described, and compared in a table with the type species of the genus from the south east of Brazil, C. agriliformis (Kerremans, 1897). They are clearly distinguishable by differences in color and form. Both species are illustrated.